Analisis Penerapan Corporate Social Responsibility Dalam Upaya Pengembangan Masyarakat (Studi Kasus Program Kemitraan Bank Jateng Pada SPT Bubakan) - Achmad Kurniawan; Wahyu Hidayat; Sri Suryoko (Universitas Diponegoro, 2015)
The research was motivated by the diverse motives of corporate in carrying out the activity of CSR. The interesting problem in this research is the existence of a partnership program since 2009. The partnership program more directed in the form of Bank Jateng CSR activities as a community development while the previous CSR activities only just a charity. This research is a qualitative study descriptive using the strategies case study. Data collection methods used is interviews, observations and document, to the withdrawal data or sample while using a technique of purposive sampling and snowball sampling. Total informants on this research has 9 people. A case study in this research is a partnership of the farm empowerment center bubakan in hamlet Kuncen village Bubakan Mijen sub-district , the city of Semarang, With the main program durian kholil development.The results showed that the stages of implementation of CSR especially the partnership with Bank of Central Java program . There are three stages namely : (1) the planning stage (2) the stage of implementation (3) the evaluation phase. The largest obstacles from the three stages mentioned above is limited human resources in the management of CSR. To handle the problem, Bank Jateng asked for help with branches as well as communicate with its companion and partner under the jurisdiction. The conclusion of this research is the planning stage of Bank Jateng csr including into the Bottom Up Process. At this stage of the implementation of the Bank Jateng using two models named directly engagement and partnering with other parties. At this stage, the evaluation of Bank Jateng incorporates reporting within. CSR implementation (partnership program) on the SPT Bubakan can be said to have not been as community development, this is apparent from the community is not fully involved in the planning of activities.